Balancing expressiveness and inexpressiveness in view design - Benedikt, M; Bourhis, P; Jachiet, L; Tsamoura, E (IJCAI Organization, 2020)
We study the design of data publishing mechanisms that allow a collection of autonomous distributed datasources to collaborate to support queries. A common mechanism for data publishing is via views: functions that expose derived data to users, usually specified as declarative queries. Our autonomy assumption is that the views must be on individual sources, but with the intention of supporting integrated queries.